Synthesis and characterization of several local anaesthetics - Alnadeesh, Faten Mohammed Hezam (2013)
Three local anaesthetics, tetracaine, lidocaine and benzocaine were synthesized and characterized. Tetracaine or 2-(diethylamino)ethyl 4-butylaminobenzoate was synthesized using two approaches. The first approach was a direct esterification of 4-butylaminobenzoic acid with 2-(diethylamino)ethanol in the presence of boron trifluoride etherate as catalyst to afford 2-(diethylamino)ethyl 4-butylaminobenzoate. The second approach involved two step reactions. Treatment of 4-butylaminobenzoic acid with ethanol in the presence of boron trifluoride etherate afforded ethyl 4-butylaminobenzoate in the first step, followed by, transesterification of ethyl 4-butylaminobenzoate with 2-(diethylamino)ethanol to afford 2-(diethylamino)ethyl 4-butylaminobenzoate in the second step. Lidocaine or 2-(diethylamino)-N-(2,6-dimethylphenyl)acetamide was synthesized from 2,6-dimethylaniline, a-chloroacetyl chloride, diethylamine, with a-chloro-2,6-dimethylacetanilide being intermediate in the synthesis. Benzocaine or ethyl-4-aminobenzoate was synthesized by Fischer esterification of 4-aminobenzoic acid with absolute ethanol. The intermediates and products were characterized by using infrared (IR), proton nuclear magnetic resonance (1H NMR), and carbon nuclear magnetic resonance (13C NMR) spectroscopies.